2008
DOI: 10.1021/es800167g
|View full text |Cite
|
Sign up to set email alerts
|

Metal Solubility and Speciation in the Rhizosphere of Lupinus albus Cluster Roots

Abstract: The objective of this study was to investigate the influence of root exudation of organic acid anions on the speciation of major and trace metal cations in the rhizosphere of Lupinus albus cluster roots. Plants were grown in rhizoboxes containing repacked weakly acidic loam. Bulk soil solutions and, during the lifetime of cluster roots, rhizosphere solutions were collected using micro suction cups. During organic acid anion exudation bursts, metals in the rhizosphere of cluster roots were strongly mobilized. T… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
30
1

Year Published

2008
2008
2020
2020

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 48 publications
(33 citation statements)
references
References 40 publications
2
30
1
Order By: Relevance
“…The different chemical and biological conditions of the rhizosphere with respect to the bulk soil can change metal fractions and therefore bioavailability of metals (Dessureault-Rompre et al, 2008;Tao et al, 2003). Moreover, low-molecular-weight organic acids produced by plant roots exudation and bacterial metabolism are involved in many processes operating in the rhizosphere, including nutrient acquisition, metal detoxification, and alleviation of anaerobic stress in roots (Jones, 1998 speciation and transportation of Zn in the rhizosphere soil.…”
Section: Different Mathematical Modelsmentioning
confidence: 99%
“…The different chemical and biological conditions of the rhizosphere with respect to the bulk soil can change metal fractions and therefore bioavailability of metals (Dessureault-Rompre et al, 2008;Tao et al, 2003). Moreover, low-molecular-weight organic acids produced by plant roots exudation and bacterial metabolism are involved in many processes operating in the rhizosphere, including nutrient acquisition, metal detoxification, and alleviation of anaerobic stress in roots (Jones, 1998 speciation and transportation of Zn in the rhizosphere soil.…”
Section: Different Mathematical Modelsmentioning
confidence: 99%
“…Citrate concentrations can reach mM levels in the rhizosphere solution of cluster roots (Dessureault-Rompré et al 2008). Gardner et al (1982) showed that white lupin grown on an alkaline soil also responds to iron stress by the development of a higher proportion of cluster roots and an increase in proton and reducing and chelating compound production.…”
Section: Introductionmentioning
confidence: 99%
“…One is the use of rhizoboxes in combination with micro-suction cups (Göttlein et al 1996) which were already used with different plants and soils (Wenzel et al 2001;Dessureault-Rompré et al 2008;Gao et al 2009). In the present study we determined in situ Zn and P mobilization by citrate in the rhizosphere of calcareous soils and linked potential Zn and P mobilization to plant uptake and the results of a nutrient solution and a soil extraction experiment.…”
Section: Introductionmentioning
confidence: 99%
“…5). Many of them can be accumulated and eventually concentrated in the edible parts of crops, depending on their speciation, solubility and bioavailability and by the ability of a crop to take up the essential and non-essential elements and translocate them to the target organs (Burgos et al 2008;Clemente et al 2008;Dessureault-Rompre et al 2008;Almendras et al 2009;Quartacci et al 2009). Metals can be absorbed by plants, wildlife and people through the food they eat.…”
Section: Soil Contamination By As Co Cr and Pb In An Alpine Territomentioning
confidence: 99%